What to Do When Foreign Direct Investment Is Not Direct or Foreign : FDI Round Tripping - Aykut, Dilek; Sanghi, Apurva; Kosmidou, Gina (World Bank, Washington, DC, 2017)
As globalization has intensified, multinational enterprises' investments have become a sophisticated set of financial transactions that are difficult to monitor and classify by the home and host countries. In some cases, what is classified as foreign direct investment is rather "indirect foreign direct investment," channeled through a third country. Indirect flows have increased significantly in recent years, now accounting for almost 30 percent of global foreign direct investment flows. Indirect foreign direct investment flows also capture the flow of domestic funds channeled through offshore centers back to the local economy in the form of direct investment, also known as "foreign direct investment round tripping." These investments do not offer the benefits of typical foreign direct investment, and may lead to tax revenue and welfare losses. Round tripping is mostly channeled through offshore financial or transshipping centers. In most cases, domestic companies round trip their investments to benefit from preferential treatments reserved for certain countries and their firms. The most important policy measure to reduce round tripping activity and mitigate its impact is to improve the business environment for all firms; this can foster domestic and foreign investment, and may, to some extent, also curb foreign direct investment round tripping. Nevertheless, countries also need to adapt to the new playing field for foreign direct investment, and recognize the trade-offs of their national policies on capital flows. National policy measures must be complemented by international actions. At the same time, all indirect foreign direct investment flows should be closely monitored, something that is best conducted in coordination with international partners.